Estimation Model of Ramin (Gonystylus bancanus) Standing Stock in Peat Swamp Forest: Case Study in Sumatra and Kalimantan - Samsuri, Samsuri; Jaya, I Nengah Surati; Lastini, Tien; Purnama, Edwin Setia (Talenta Publisher, 2018)
Multiple sampling technique was applied to estimate ramin (Gonystylus bancanus) standing stock in peat swamp forest by combining imagery analysis (phase I) and field measurement (phase II). The objectives of this research were to obtain (1) estimation model of stand volume, (2) estimation model of G. bancanus standing stock, and (3) volume of standing stock of G. bancanus in Sumatera and Kalimantan peat swamp forests. The research was conducted in peat swamp forest of Sumatera and Kalimantan Island. ALOS AVNIR image interpretation was completed to obtain crown density and used as independent variable for developing stand volume model. Cluster sampling was used to obtain field data from circle sample plot of 0.1 ha and square sample plot of 0.25 ha. Spatial analysis was conducted to map and calculate standing stock of G. bancanus for Sumatera and Kalimantan Island. Estimation model of stand volume was V bf = 0.1851 C field1.05234 (R 2 =0.62) for Sumatera peat swamp forest and V bf = 3.1163 e 0.041 Cfield (R 2 = 0.62) for Kalimantan peat swamp forest, respectively. We estimated that standing stock of G. bancanus of peat swamp forest in Sumatra and Kalimantan was 5% and 2.3% of the total stand volume, respectively. Base on both the estimation models, standing stock of G. bancanus in Sumatera peat swamp forest was 15,351,063 m 3 and in Kalimantan peat swamp forest was 6,004,874 m 3 .